A Critical Discourse Analysis of COVID-19 in Ethiopia: Rethinking the Past and Defining the Present - Daniel Tiruneh; Getachew Baye; Yosef Beco Dubi (Universitas Sanata Dharma, 2020)
The purpose of this study is to unearth the landscape of social media and analyse the contents. Contents of social media, in Ethiopia, are varying over the course of changes in politics, health, socio-economic conditions of the country. Some of the contents are reflected in the forms of narratives, comments, briefings, anecdotes, and verses to list a few. Contents changing the way people interact with each other and share information, personal messages, and opinions about situations, objects, and past experiences- rethinking the past, themes are linked to the present and define the present Ethiopia. In order to attain the stated objective, the researchers developed critical discourse analysis as a research methodology and adapted Norman Fairclough’s model of Analysis as a theoretical framework. Most social media texts are short online conversational posts or comments that do not contain enough information for a full textual analysis. Therefore, using purposive sampling six excerpts were collected from various discourses of the social media platforms, particularly Facebook, Facebook messenger, and YouTube. Based on the contexts of the discourses, the analysis was categorized thematically. The study concluded that social media users used the platform as a means to reflect both the status quo of the past and linking to the current COVID-19 and its socio-economic impacts. COVID-19 is depicted as a disease, resulting from human wrongdoings, very dangerous which is deadly even to Satan. It is also depicted as a warrior, an extremely hungry predator looking for its prey, ready to eat up human being ravenous without a need for proper chewing.